Avaliação de desempenho energético de um gerador elétrico operando no modo dual, utilizando biogás e blendas de biodiesel de óleo residual de fritura - Colle, Daniel (2018)
The generation of electric energy through alternative sources of energy has been a theme constantly addressed by the researchers, both for the concern for alternatives to the energy supply and for the search of the reduction of environmental impacts in its generation. This research addresses the generation of electric energy through the use of biogas and biodiesel, both fuels from renewable sources. The performance of an electricity generator operating in dual mode with biogas and biodiesel blends was evaluated. The evaluated biodiesel was obtained from frying residual oil and experiments were performed with blends of pre-established proportions in B8 (commercial diesel - 8% biodiesel), B20 (20% biodiesel), B50 (50% biodiesel), B80 (80% biodiesel) and B100 (pure biodiesel). The biogas used came from biodigestor of swine residues. The motor generator set has a maximum power of 5.0 kVA and an output voltage of 110 and 220 V. In the tests the motor generator set was coupled to a bank of resistive loads, varying from 0 to 100% of the maximum load. Each increment was of 10%, allowing to obtain the power of generation for varied loads. The lower calorific value of biodiesel (B100) was 35912 kJ.kg-1 and biogas was 22562 kJ.m-3. The electric power generated was superior in the dual mode presenting differences of 18.76% for B8 and 21.77% for B100. The specific liquid fuel consumption was lower in the dual mode with 270.17 g.kWh-1 operating with B8 and 285.29 g.kWh-1 operating with B100 compared to the normal mode. The efficiency was higher in the normal mode, presenting results of 22.01% and 24.74%, operating with B8 and B100 respectively, against 17.51% and 20.18% in the dual mode. The average fuel economy for the B8 blend was 30.06% and 30.08% for B100 in dual mode over the normal mode. The results indicate the possibility of the use of biodiesel from frying waste oil in normal mode, as well as its use in dual mode together with biogas.